BIOCHEMICAL CHARACTERIZATION AND PROTEIN PROFILE BY SDS-PAGE OF FRENCH BEAN (PHASEOLUS VULGARIS L.) ASSOCIATED RHIZOBIA - B, NAGA NIRMALA KUMARI; B, NAGARAJU; K, MALLIKARJUNA (Innovare Journal of Agricultural Sciences, 2018)
Â ABSTRACT Objectives: Plant growth promoting rhizobacteria are beneficial soil bacteriathat colonize plant roots and increase plant growth promotionactivity by various mechanisms in numerous ways.Nitrogen is essential element for all forms of life. Legume symbioses have asignificant role in agriculture, the plants tolerate to grow on nitrogendeprived soils and reduce the essential for nitrogen inputs for leguminous crops.French bean (Phaseolus vulgaris L.) is nodulated with numerous Rhizobium species. In the present studybiochemical characterization of 6 Rhizobium strains isolated fromFrench bean nodules collected from different regions of Andhra pradesh, India. Methods: The French bean plants were uprooted and loosely adhering soil was detached by gentle shaking. The roots along with mature nodules. Results:All the isolates of Rhizobia were positive to the Indole test, nitrate reduction test, urease, catalase test, oxidase and Mac-conkey agar test. Starch hydrolysis and gelatin hydrolysis test were positive for all isolates except Rh01 and Rh3 isolates.The maximum amount of protein content 92.22 mg/ml was recorded from Rh6 Rhizobium strain and minimum was found, 75.38 mg/ml in Rh3 Rhizobium strain. Conclusion The conclusion of the present study, the French bean rhizobial isolates to enhance the plant growth and nodulation of bean plant under the different environmental conditions Key words:Rhizobacteria,adhering,Indole test,mature nodules,protein